Consideraciones metodológicas sobre la enseñanza del Derecho y la filosofía - Herszenbaun, Miguel Alejandro (2014)
The main purpose of the present paper is to propose the employment of the "stepped method", already applied by the author at Philosophy classes, as a possible model to be followed at the teaching of law. I assert that the first step of the method -which consists in the introduction of the problems that the theory seeks to resolve-, should be adopted in the teaching process. Thus, the starting point in the learning process is a number of questions posed by the students. The answers to them are expected to be found in the content of the curricula. In this way, students achieve a stronger base to understand the contents of the subject and, at the same time, they become able to evaluate in a scientifically and critically way if the discipline or the theory provides the corresponding answers and solutions to the problems initially identified or if it needs to be reformulated.